Controlled ring-opening polymerisation of cyclic phosphates, phosphonates and phosphoramidates catalysed by heteroleptic BHT-alkoxy magnesium complexes. Issue 44 (30th October 2017) - Nifant'ev, I. E.; Shlyakhtin, A. V.; Bagrov, V. V.; Komarov, P. D.; Kosarev, M. A.; Tavtorkin, A. N.; Minyaev, M. E.; Roznyatovsky, V. A.; Ivchenko, P. V.
Abstract : BHT-Mg-alkoxides are readily available and effective ROP catalysts for cyclic ethylene phosphate monomers and outperform conventional organocatalysts in versatility. Abstract : We report here that the heteroleptic BHT-Mg(OR) complex, i.e. [(BHT)Mg(OBn)(THF)]2 (Mg3 ), represents an effective and versatile ring-opening polymerisation (ROP) catalyst for several cyclic ethylene phosphate monomers (CEPMs), such as ethylene phosphates with methoxy- (MeOEP, 1 ), isopropoxy- ( i PrOEP, 2 ), and tert -butoxy- ( t BuOEP, 3 ) substituents, N, N -diethyl ethylene phosphoramidate (Me 2 NEP, 4 ) as well as ethyl (EtPPn, 5 ) and tert -butyl ( t BuPPn, 6 ) ethylene phosphonates.Mg3 retains its catalytic activity over a broad temperature range from −50 to 100 °C and efficiently carries out the fast and controlled polymerisation of CEPMs with sterically unhindered alkoxy groups with less than 1% chain branching even at near-complete conversion. Compared with ROP catalysed by 1, 5, 7-triazabicyclo[4.4.0]dec-5-ene (TBD ), Mg3 performs much better in the polymerisation of CEPMs with bulky groups and of monomers sensitive to strong nucleophiles, such as t BuOEP .